Molecular commensalism: how oral corynebacteria and their extracellular membrane vesicles shape microbiome interactions - Kreth, Jens; Helliwell, Emily; Treerat, Puthayalai; Merritt, Justin (Frontiers in Oral Health, 2024)
Historically, the study of microbe-associated diseases has focused primarily on pathogens, guided by Koch's postulates. This pathogen-centric view has provided a mechanistic understanding of disease etiology and microbial pathogenesis. However, next-generation sequencing approaches have revealed a far more nuanced view of the roles various microbes play in disease, highlighting the importance of microbial diversity beyond individual pathogens. This broader perspective acknowledges the roles of host and microbial communities in disease development and resistance. In particular, the concept of dysbiosis, especially within the oral cavity, has gained attention for explaining the emergence of complex polymicrobial diseases. Such diseases often stem from resident microbes rather than foreign pathogens, complicating their treatment and even clouding our understanding of disease etiology. Oral health is maintained through a delicate balance between commensal microbes and the host, with diseases like caries and periodontal disease arising from pathogenic perturbations of this balance.Commensal microbes, such as certain streptococci and Corynebacterium spp., play crucial roles in maintaining oral health through mechanisms involving hydrogen peroxide production and membrane vesicle secretion, which can inhibit pathogenic species and modulate host immune responses. Recent research focused upon the mechanisms of molecular commensalism has expanded our understanding of these key functions of the commensal microbiome, demonstrating their central role in promoting oral health and preventing disease. These abilities represent a largely untapped reservoir of potential innovative strategies for disease prevention and management, emphasizing the need to bolster a symbiotic microbiome that inherently suppresses pathogenesis.